2014
DOI: 10.5114/hpr.2014.42787
|View full text |Cite
|
Sign up to set email alerts
|

Key factors for successful solving of mathematical word problems in fifth-grade learners

Abstract: health psychology report • volume (), 4 original article background Difficulties in solving mathematical word problems (MWP) are one of the most common reasons for weak mathematics performance, and poor mathematical literacy has important implications for an individual's further education, employment opportunities, mental health and quality of life in today's modern technological society. The purpose of the study was to examine whether Slovenian good and poor MWP solvers differ in arithmetic knowledge and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…So, Mushlihah Rohmah, Sugeng Sutiarso, Lampung University [9] focused their attention on studying the types of mistakes that students make while solving math problems. Slovenian scholars Kavkler, M., Magajna, L. and Kosak Babuder, M. [10] investigated the differences in the solving of mathematical word problems by students with MLD (mathematical learning difficulties) and successful solvers of MWP (mathematical word problem). Mary Hegarty, Richard E. Mayer, and Christopher A. Monk, University of California [11] studied the problem of understanding the text of mathematical problems.…”
Section: The Process Of Solving Mathematical Word Problemsmentioning
confidence: 99%
“…So, Mushlihah Rohmah, Sugeng Sutiarso, Lampung University [9] focused their attention on studying the types of mistakes that students make while solving math problems. Slovenian scholars Kavkler, M., Magajna, L. and Kosak Babuder, M. [10] investigated the differences in the solving of mathematical word problems by students with MLD (mathematical learning difficulties) and successful solvers of MWP (mathematical word problem). Mary Hegarty, Richard E. Mayer, and Christopher A. Monk, University of California [11] studied the problem of understanding the text of mathematical problems.…”
Section: The Process Of Solving Mathematical Word Problemsmentioning
confidence: 99%
“…The importance of mathematical knowledge in this technological time is recognised globally, for it is a tool for developing a rational personality (Kavkler et al, 2014). Problem-solving is widely acknowledged as a pivotal skill that nurtures critical thinking, logical reasoning, and the practical application of mathematical principles (Polya, 1945;Schoenfeld, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Hence underscoring the necessity of prioritising the thorough teaching and learning of its core concepts. Drawing upon this particular viewpoint and the scholarly research conducted by Kavkler et al (2014), which has systematically demonstrated the benefits of the subject, it is justifiable to argue that providing young pupils with a comprehensive comprehension of mathematics continues to be of utmost importance. This responsibility should be embraced by all educators in the field.…”
Section: Introductionmentioning
confidence: 99%
“…This world, for some time, now has put so much emphasis on science and technology. Kavkler, Magajna and Babuder (2014) have postulated that mathematics in this technological era become an essential tool for developing rational human personality. That is, mathematical knowledge develops in people critical thinking for most especially life and career decisions.…”
Section: Introductionmentioning
confidence: 99%